2017
DOI: 10.1113/jp274865
|View full text |Cite
|
Sign up to set email alerts
|

Laminar‐specific encoding of texture elements in rat barrel cortex

Abstract: Texture discrimination by rats is exquisitely guided by fine-grain mechanical stick-slip motions of the face whiskers as they encounter, stick to and slip past successive texture-defining surface features such as bumps and grooves. Neural encoding of successive stick-slip texture events will be shaped by adaptation, common to all sensory systems, whereby receptor and neural responses to a stimulus are affected by responses to preceding stimuli, allowing resetting to signal novel information. Additionally, when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 72 publications
(315 reference statements)
2
18
0
Order By: Relevance
“…As a result, electrophysiological data from 31 sessions were included in the analysis, as follows: 16 sessions in which the microelectrode sampled activity from superficial layers (,0.9 mm from cortical surface, mainly layers II-IV) and 15 sessions in which the microelectrode-sampled activity from deep layers (.1.1 mm from cortical surface, mainly layers V/VI). The rationale for looking separately at data sampled from superficial and deep layers was the fact that gammaband oscillations are more prominent in superficial layers, where local recurrent connections are more abundant than in deep layers (Allitt et al, 2017;Bruyns-Haylett et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, electrophysiological data from 31 sessions were included in the analysis, as follows: 16 sessions in which the microelectrode sampled activity from superficial layers (,0.9 mm from cortical surface, mainly layers II-IV) and 15 sessions in which the microelectrode-sampled activity from deep layers (.1.1 mm from cortical surface, mainly layers V/VI). The rationale for looking separately at data sampled from superficial and deep layers was the fact that gammaband oscillations are more prominent in superficial layers, where local recurrent connections are more abundant than in deep layers (Allitt et al, 2017;Bruyns-Haylett et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The use of high-speed imaging techniques has allowed the study of kinematics at elevated temporal and spatial resolutions as the whiskers of an awake rat or mouse come into contact with a surface. A consensus is forming that the critical element supporting texture discrimination is the stick-slip event [1,9,[14][15][16][17][18]. This may also be true for fingertips, where lateral forces create stick-slip skin micromotion that is especially effective in exciting primary afferents [16,19,20].…”
Section: Texture Coding Through Whisker Kinematicsmentioning
confidence: 99%
“…Several in vivo studies have already established that at least some S1 neurons -depending on their afferent input (Saal et al, 2015) -respond to vibrotactile stimuli with precisely times spikes (Allitt et al, 2017;Arabzadeh et al, 2005;Ewert et al, 2015;Ewert et al, 2008;Harvey et al, 2013;Jadhav et al, 2009;Lieber and Bensmaia, 2019). The rate of those spikes can also carry information; for instance, Jadhav et al (2009) found that firing rate and synchrony both increase with roughness, but synchrony varied more consistently than rate for subtle differences in texture.…”
Section: Discussionmentioning
confidence: 99%